2019
DOI: 10.1016/j.ajog.2019.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing shorter cfDNA fragments improves the fetal DNA fraction in noninvasive prenatal testing

Abstract: BACKGROUND: Sequencing cell-free DNA in maternal plasma is an effective noninvasive prenatal testing technique that has been used in fetal aneuploidy screening worldwide. However, its clinical application is limited by the low fetal fraction (<4%) of cell-free DNA in many singleton pregnancies, which usually results in screen failures or no calls. In addition, dizygotic twin contributions of cell-free DNA into the maternal circulation can vary by 2-fold, complicating the quantitative diagnosis of fetal aneuplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…25,26 FF also negatively correlates with firsttrimester body mass index (BMI) and maternal age, 27 but these values are effectively constant for any given pregnancy. At the molecular level, it has been observed that fetal-derived cfDNA fragments tend to be shorter, 28,29 hypermethylated, [30][31][32] and enriched at different locations than maternal cfDNA fragments. 33 Leveraging these biases at the molecular and bioinformatic levels has the potential to multiplicatively boost the FF of every sample.…”
Section: Platforms)mentioning
confidence: 99%
“…25,26 FF also negatively correlates with firsttrimester body mass index (BMI) and maternal age, 27 but these values are effectively constant for any given pregnancy. At the molecular level, it has been observed that fetal-derived cfDNA fragments tend to be shorter, 28,29 hypermethylated, [30][31][32] and enriched at different locations than maternal cfDNA fragments. 33 Leveraging these biases at the molecular and bioinformatic levels has the potential to multiplicatively boost the FF of every sample.…”
Section: Platforms)mentioning
confidence: 99%
“…25,26 FF also negatively correlates with firsttrimester BMI and maternal age, 27 but these values are effectively constant for any given pregnancy. At the molecular level, it has been observed that fetal-derived cfDNA fragments tend to be shorter, 28,29 hypermethylated, [30][31][32] and enriched at different locations than maternal cfDNA fragments. 33 Leveraging these biases at the molecular and bioinformatic levels has the potential to multiplicatively boost the FF of every sample.…”
Section: Platforms)mentioning
confidence: 99%
“…FF herein is measured either via a regression on autosomal bin depth 36 or from the normalized depth of next-generation sequencing (NGS) data for a particular region (e.g., chrY, chr21, etc.). The proprietary FFA technology leverages the reduced size of fetal-derived cfDNA molecules-observed in several reports 28,29,37 -to increase the relative abundance of fetal cfDNA. Extracted cfDNA is quantified and then size selected by agarose gel electrophoresis such that the average length of selected cfDNA fragments is 140nt, which preferentially retains fetal cfDNA and depletes maternal cfDNA ( Figure S1).…”
Section: Ffa Validationmentioning
confidence: 99%
“…In this study, we confirmed that prediction based on combined clinical and laboratory indicators using machine learning algorithm is more effective. For the positive prediction, sequencing shorter cfDNA fragments or cfDNA enrichment can be used to improve the FF of NIPS [24]. Furthermore, there was a large number of missing values in the raw clinical data set in which directly filtering of missing values will result in insufficient specimens for subsequent analysis.…”
Section: Discussionmentioning
confidence: 99%